Analisis Sosiolinguistik: Perspektif Bahasa Dalam Masyarakat - Rivandi Anju Gurning; Widia Wati Sipayung; Elsah Sinurat; Yuliana Sari Saragih (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to examine the relationship between language and society through a sociolinguistic perspective, focusing on language variations that are influenced by social factors such as class, gender, ethnicity and age. Using the literature review method, this research analyzes various previous studies that discuss language variations, dialects, social identities, and the role of bilingualism in multicultural societies. The research results show that language not only functions as a means of communication, but also as a reflection of social identity, culture and power. Variations in language use, whether in the form of dialect, style, or register, reflect social stratification and power relations in society. In addition, the phenomena of bilingualism and language shift highlight the dynamics of interactions between national languages ​​and regional languages, with potential threats to the survival of regional languages. This research concludes that a deep understanding of language variation is important for preserving linguistic and cultural richness. The limitations of the literature review method underscore the need for further research to enrich sociolinguistic studies.